2015
DOI: 10.1246/cl.141094
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase Ozone Reactions with Z-3-Hexenal and Z-3-Hexen-1-ol: Formation Yields of OH Radical, Propanal, and Ethane

Abstract: The formation yields of OH radical, propanal, and ethane from the reactions of ozone with Z-3-hexenal (3HA) and Z-3-hexen-1-ol (3HO) were measured under atmospheric conditions. These OH yields were determined to be 0.32 « 0.07 for 3HA and 0.28 « 0.06 for 3HO. The relative formation yield of the C 2 H 5 CHOO intermediate was estimated based upon the formation yields of propanal and ethane, which consistently suggested that C 2 H 5 CHOO is formed more efficiently from the O 3 + 3HA reaction than from the 3HO rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
(12 reference statements)
1
6
0
Order By: Relevance
“…Further, studies carried out on the ozonolysis of oxygenated alkenes indicate that the decomposition of the primary ozonide displays a preference for the pathway yielding an oxygenated carbonyl [46][47][48] . Hence, the formation of the alkyl-substituted bi-radical and the formation of glyoxal could be favored.…”
Section: Comparison With Literature Datamentioning
confidence: 99%
“…Further, studies carried out on the ozonolysis of oxygenated alkenes indicate that the decomposition of the primary ozonide displays a preference for the pathway yielding an oxygenated carbonyl [46][47][48] . Hence, the formation of the alkyl-substituted bi-radical and the formation of glyoxal could be favored.…”
Section: Comparison With Literature Datamentioning
confidence: 99%
“…This observation has consequences for the interpretation of the preferred fragmentation channel of the primary ozonide and is discussed further below. Additionally, Uchida et al 27 in their study of the ozonolysis of (Z)-3-hexenal proposed that the alkyl chain biradical can decompose through two pathways. Based on their work, the alkyl substituted biradical of the ozonolysis reaction under study CH 3 (CH 2 ) n C • HOO • (n = 3, 4 or 5) can undergo the following decomposition pathway: However, as stated above, we did not observe variations in the CO or CO 2 concentrations in our experimental conditions.…”
Section: ■ Experimental Setupmentioning
confidence: 99%
“…Paulson et al 40 have determined an OH yield of 16% for the ozonolysis of methyl vinyl ketone (CH 2 CHC(O)CH 3 ), and Uchida et al 27 have reported an OH formation yield of 32% for the ozonolysis of (Z)-3-hexenal (CH 3 CH 2 CH CHCH 2 C(O)H). Since in our ozonolysis systems it would appear, based on the discussion above, that only the CH 3 (CH 2 ) n C • HOO • (n = 3, 4, or 5) Criegee biradicals will be producing OH, based on the work of Uchida et al 27 we estimate that OH radical production is probably of the order of 15% or less.…”
Section: ■ Experimental Setupmentioning
confidence: 99%
See 2 more Smart Citations